Curcumin - The Nutraceutical With Pleiotropic Effects? Which Cardiometabolic Subjects Might Benefit the Most? - Surma, Stanisław; Sahebkar, Amirhossein; Urbański, Jakub; Penson, Peter E.; Banach, Maciej (Frontiers in Nutrition, 2022)
Despite continuous advances in pharmacotherapy, atherosclerotic cardiovascular disease remains the world's leading killer. Atherosclerosis relates not only to an increased level of cholesterol, but involves the development of atherosclerotic plaques, which are formed as a result of processes including inflammation and oxidative stress. Therefore, in addition to the classical risk factors for ASCVD (such as type 2 diabetes, overweight, obesity, hypertension and metabolic syndrome), residual risk factors such as inflammation and oxidative stress should also be reduced. The most important intervention in ASCVD is prevention, which includes promoting a healthy diet based on products of natural origin. Curcumin, which is often present in the diet, has been demonstrate to confer several benefits to health. It has been shown in numerous clinical trials that curcumin exhibited anti-diabetic, lipid-lowering, antihypertensive, antioxidant and anti-inflammatory effects, as well as promoting weight loss. All this means that curcumin has a comprehensive impact on the most important risk factors of ASCVD and may be a beneficial support in the treatment of these diseases. Recently, it has also been shown that curcumin may have a beneficial effect on the course of SARS-CoV-2 infection and might be helpful in the prevention of long-COVID complications. The aim of this review is to summarize the current knowledge regarding the safety and efficacy of curcumin in the prevention and treatment of cardiometabolic diseases.